Impact of Crisaborole on Sleep Outcomes in Pediatric Patients with Mild-to-Moderate Atopic Dermatitis - Joseph Fowler; Jeffrey Sugarman; Lawrence Sher; Chuanbo Zang; John L. Werth; Daniela E. Myers; Daniela Graham; Alexander Agyei Marfo; Liza Takiya (Dermatology and Therapy, 2023)
Plain Language Summary Atopic dermatitis (AD), also known as eczema, is a chronic skin disease that causes red or flaky skin patches that can become infected and itch. Children with AD often experience sleep disturbance, including difficulty falling asleep, restless sleep, waking up more frequently, and daytime drowsiness. Problems with sleep quality negatively impact children with AD, as well as their caregivers. Crisaborole ointment is applied to the skin and has been shown to improve the symptoms of AD in children and adults. This study examined how treatment with crisaborole affected sleep quality for children and their caregivers in three clinical trials. Children in these studies took crisaborole for 28 days. Researchers found that crisaborole treatment improved sleep in children with mild-to-moderate AD and their caregivers. This was determined using four measures. First, a smaller proportion of children who were treated with crisaborole experienced sleep disruption compared with those to whom a vehicle was applied (an ointment with no drug). Second, a smaller proportion of caregivers of children with AD who were treated with crisaborole reported effects on their sleep, compared with children to whom a vehicle was applied. Third, a smaller proportion of children with AD who were treated with crisaborole, as well as their caregivers, had ≥ 1 night per week of disturbed sleep after treatment compared with before treatment. Fourth, the caregivers of children treated with crisaborole reported significantly less exhaustion and tiredness because of the child’s AD. These results suggest that treatment with crisaborole improves sleep outcomes in children with mild-to-moderate AD and their caregivers.